Does maternal hyperoxygenation have any effect on the fetal circulatory system in normal growth and late-onset IUGR fetuses? (Annals of Medical Research, 2023)
Aim: Maternal hyperoxygenation (MHO) has been recommended as an alternative treatment for fetuses with IUGR. We wanted to evaluate the effect of MHO treatment on ductus venosus (DV) and pulmonary vein (PV) doppler flow measurements in fetuses with late-onset IUGR.Materials and Methods: A total of 63 pregnant women were enrolled in the study (32 pregnant women diagnosed with IUGR and 31 women with normal growth). The control group comprised 31 randomly selected age-matched and gestational-age-matched healthy pregnant women who presented to the antenatal clinic on the exact dates as the women in the study group.Results: In the IUGR group, MHO significantly increased the PI value of DV (0.50 (0.40, 0.58) to 0.62 (0.60, 0.65). p
Keywords: Maternal hyperoxygenation; Fetal echocardiography; Intrauterine growth retardation